Is the negative interest rate policy effective? - Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2019)
This paper examines the effectiveness of the negative interest rate policy conducted by several central banks to stabilize economic growth and in ation expectations through the signaling channel. In doing so, we assess survey-based expectations data for up to 44 economies from 2002 to 2017 and analyze the impact of the adoption of a negative interest rate policy on expectations made by professionals based on a difference-in-differences approach. Our main findings are as follows: First, we show that the introduction of negative policy rates signi ficantly reduces expectations regarding 3-month money market interest rates and also 10-year government bond yields. Second, we also provide evidence for a significantly positive effect of this unconventional monetary policy tool on GDP growth and in ation expectations. This implies that the negative interest rate policy appears to be effective in boosting economic growth and overcoming a de- ationary spiral. Consequently, the effect of negative nominal interest rates on real interest rate expectations is also negative.
Keywords: E31; E43; E52; 330; Expectations; Ination; Monetary policy; Negative interest rates; Survey data